2016
DOI: 10.1152/ajpendo.00319.2015
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic phenotype and adipose and liver features in a high-fat Western diet-induced mouse model of obesity-linked NAFLD

Abstract: Luo Y, Burrington CM, Graff EC, Zhang J, Judd RL, Suksaranjit P, Kaewpoowat Q, Davenport SK, O'Neill AM, Greene MW. Metabolic phenotype and adipose and liver features in a high-fat Western diet-induced mouse model of obesity-linked NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 45 publications
3
46
1
Order By: Relevance
“…[43][44][45] Particularly, pervious researches have suggested that excess intake of fat-rich diet may cause hyperlipemia and intestinal endotoxemia, resulting in blood lipid metabolism disorder and systemic inflammation, ultimately contributing to the development of CKD and NAFLD. [46][47][48] Thus, kidney disease caused by eating habits has widely received enough attention by the researchers. HFD-induced metabolic abnormalities would change kidney-related gene expression …”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45] Particularly, pervious researches have suggested that excess intake of fat-rich diet may cause hyperlipemia and intestinal endotoxemia, resulting in blood lipid metabolism disorder and systemic inflammation, ultimately contributing to the development of CKD and NAFLD. [46][47][48] Thus, kidney disease caused by eating habits has widely received enough attention by the researchers. HFD-induced metabolic abnormalities would change kidney-related gene expression …”
Section: Discussionmentioning
confidence: 99%
“…The entire surface area of each fat pad was counted to provide a total number of crown‐like structures per fat pad. Adipocyte area was determined as previously described .…”
Section: Methodsmentioning
confidence: 99%
“…In a study by Luo et al, researchers used a WD mouse model that consisted of high fat content (40% of energy from fat with 30% of fat from lard, 30% from butterfat, and 30% from Crisco) and liquid fructose and sucrose (42 g/L total at a ratio of 55% fructose to 45% sucrose) 75 . Researchers found that this diet caused increased glucose intolerance, insulin resistance and adipose tissue dysfunction 75 . In addition, there were increased levels of intrahepatic triglycerides, plasma ALT, liver weight, hepatic fibrosis and hepatic inflammation 75 .…”
Section: Western-like Diet (Wd)mentioning
confidence: 99%
“…Researchers found that this diet caused increased glucose intolerance, insulin resistance and adipose tissue dysfunction 75 . In addition, there were increased levels of intrahepatic triglycerides, plasma ALT, liver weight, hepatic fibrosis and hepatic inflammation 75 . This diet resulted in similar results as the WD consisting of high fat, cholesterol, and one type of sugar (either fructose or glucose) making it a reasonable mouse model option as it also induced NASH with fibrosis and features of metabolic syndrome.…”
Section: Western-like Diet (Wd)mentioning
confidence: 99%